2014
DOI: 10.1166/jbn.2014.1762
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cortical Neuronal Survival During Liver Injury: Effect of Gamma Aminobutyric Acid and 5-HT Chitosan Nanoparticles

Abstract: Use of nanoparticulate drug delivery system for an effective therapeutic outcome against diseases gains immense hope in the study of drug delivery to partially hepatectomised rats. In the present study, partially hepatectomised rats treated with Gamma aminobutyric acid (GABA) and serotonin (5-HT) chitosan nanoparticles, individually and in combination, were evaluated to analyse their role in GABAB, and 5-HT2A receptors functional regulation, interrelated neuronal survival mechanisms by nuclear factor kappa B (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 38 Furthermore, in rats with liver injury, 5-HT 2A and GABA B2 directly repressed CREB expression, exerting protective effects on liver neurons. 39 Increased CREB phosphorylation in the dorsal horn resulted in an increase in histone H4 acetylation in the CDK5 promoter and upregulated CDK5 transcription, so suppressed CREB expression reduced CDK5 growth and relieved rat mechanical allodynia. 13 Importantly, it was previously indicated that dysregulated H19 can directly or indirectly modulate many different carcinogenic factors, including CDK.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Furthermore, in rats with liver injury, 5-HT 2A and GABA B2 directly repressed CREB expression, exerting protective effects on liver neurons. 39 Increased CREB phosphorylation in the dorsal horn resulted in an increase in histone H4 acetylation in the CDK5 promoter and upregulated CDK5 transcription, so suppressed CREB expression reduced CDK5 growth and relieved rat mechanical allodynia. 13 Importantly, it was previously indicated that dysregulated H19 can directly or indirectly modulate many different carcinogenic factors, including CDK.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Hou (2011) reported that GABA prevented kainic acid (KA)-induced neuronal injury by suppressing lipid peroxidation in male FVB mice brains and inhibiting ROS accumulation in the rat's pheochromocytoma cell line (PC12). Moreover, Shilpa et al (2014) revealed that treatment of GABA and serotonin (5-HT) chitosan nanoparticles in partially hepatectomised rats were able to protect the neurons from ROS mediated cell damage and promoted their survival in the cerebral cortex by means of the regulation of the gene expression of NF-B, TNF-α, and superoxide dismutase (SOD). Therefore, the several bioactive compounds found in PGBR may suppress CCl 4 -induced liver and brain oxidative damage contributing to the inhibition of brain inflammation.…”
Section: Discussionmentioning
confidence: 99%